Refining Sound : a Practical Guide to Synthesis and Synthesizers. - Shepard, Brian K. (Oxford University Press, USA, 2013)
Refining Sound is a practical roadmap to the complexities of creating sounds on modern synthesizers. Perhaps the most difficult aspect of learning to create sounds on a synthesizer is understanding what all the individual synthesizer components contribute to the complex finished sound. Author and veteran synthesizer instructor Brian K. Shepard draws on his years of experience in synthesizer pedagogy in order to peel back the often-mysterious layers of sound synthesis one-by-one. The result is a book that allows readers to familiarize themselves with each individual step in the synthesis proces.